Evaluation of the frequency of adrenal crises and preventive measures in patients with primary and secondary adrenal insufficiency in Switzerland (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY Adrenal insufficiency is a dangerous clinical condition, leading to significant morbidity or mortality in situations with inadequate glucocorticoid replacement treatment. We aimed to assess preventive measures in adrenal insufficiency and the incidence and risk factors of adrenal crisis, as well as to test the patients’ knowledge about their disease. METHODS All patients in May and June 2016 and December 2016 and January 2017 with primary (17.9%) or secondary (82.1%) adrenal insufficiency were prospectively included in this observational study. They completed questionnaires about their personal and medical background, including the occurrence of adrenal crises, and possession of an emergency card and medication. They were asked about self-perceived subjective knowledge of their disease and filled out two multiple-choice tests about the modalities of the glucocorticoid replacement therapy (test A) and dose adaptation in hypothetical clinical situations (test B) in order to objectively test their knowledge. RESULTS A total of 56 datasets were available for descriptive and statistical analysis. Overall, 94.6% of the patients were equipped with an emergency card, 64.3% had their daily hydrocortisone with them and 57.1% carried spare hydrocortisone pills. Twelve patients had experienced at least one adrenal crisis. There were 4.4 adrenal crises per 100 disease-years. Precipitating causes for adrenal crises were mainly gastroenteritis, influenza and noncompliance. Globally, the patients’ self-perceived, subjective knowledge level was good to very good. In the two objective knowledge tests, however, only 28.9% (test A) and 60.1% (test B) of the questions were answered correctly. Secondary adrenal insufficiency reduced the chance of being in the group with better knowledge in test A. CONCLUSIONS The incidence of adrenal crisis in Switzerland is lower than described in recent European studies. Although nearly all of the patients carry their emergency cards with them, emergency treatment is available in only about half of the patients. There is a mismatch between subjective and objective knowledge of the disease and the education of patients with adrenal insufficiency needs to be improved.